2015
DOI: 10.4049/jimmunol.1400789
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-Dependent Generation of a Specialized Chromatin Structure at the TCRβ Locus

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 52 publications
(98 reference statements)
5
18
0
Order By: Relevance
“…We have previously suggested that the Eα enhancer activation occurs via a conformational change of a preassembled nucleo-protein complex (Cauchy et al, 2016;Spicuglia et al, 2000). Analysis of published ChIP-seq experiments for ETS1, RUNX1, E47/TCF3, GATA3, and Ikaros lymphoid transcription factors (Zacarías-Cabeza et al, 2015;Koch et al, 2011;Lepoivre et al, 2013;Wei et al, 2011;Vanhille et al, 2015;Oravecz et al, 2015) confirmed that Eα is already occupied by these activating transcription factors in murine DN thymocytes ( Fig. S4 A).…”
Section: Dna Demethylation Is a Hallmark Of Distal Regulatory Elementsupporting
confidence: 54%
“…We have previously suggested that the Eα enhancer activation occurs via a conformational change of a preassembled nucleo-protein complex (Cauchy et al, 2016;Spicuglia et al, 2000). Analysis of published ChIP-seq experiments for ETS1, RUNX1, E47/TCF3, GATA3, and Ikaros lymphoid transcription factors (Zacarías-Cabeza et al, 2015;Koch et al, 2011;Lepoivre et al, 2013;Wei et al, 2011;Vanhille et al, 2015;Oravecz et al, 2015) confirmed that Eα is already occupied by these activating transcription factors in murine DN thymocytes ( Fig. S4 A).…”
Section: Dna Demethylation Is a Hallmark Of Distal Regulatory Elementsupporting
confidence: 54%
“…For successful V(D)J recombination to occur, the lymphoid‐specific RAG1/2 recombinases need to have access to the respective loci, and transcriptional enhancers and promoters control this process via the modulation of the chromatin structure . Moreover, it has been shown that high and extended H3K4me3 marks are present throughout the D β ‐J β ‐C β gene segments of the TCRB locus which depends on RNA polymerase II‐mediated transcriptional activity, which together with the extended H3K4 trimethylation renders D β and J β gene segments highly accessible . It is also important to note that specific TCRD gene rearrangements occur in a strict order which is dependent on RUNX proteins.…”
Section: γδ T Cells Versus αβ T Cells: What About Epigenetics?mentioning
confidence: 99%
“…In DN thymocytes, TCR gene activation for recombination depends on cooperative outputs from cis-regulatory elements, including the transcriptional enhancer E and D -flanking promoters pD s (Sikes and Oltz, 2012). At this stage, attributes of relaxed chromatin (Pol-II-generated GL transcripts, CpG demethylation, active histone marks, positioned arrays of nucleosomes) are evident in the genomic regions that encompass the D and J gene segments (Morshead et al, 2003;Kondilis-Mangum et al, 2010;Zacarias-Cabeza et al, 2015). These permit the local recruitment of RAG machinery to form a so-called recombination center (Ji et al, 2010b), and also may optimize lineagespecific release of TCR alleles from suppressive peripheral subnuclear positioning (Schlimgen et al, 2008;Chan et al, 2013).…”
Section: Modeling the Dynamics Of Tcr Recombination In Single Developmentioning
confidence: 99%